(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
The goal of this study was to conduct serosurveillance for tick-borne encephalitis virus (TBEV)in Mongolia, to isolate TBEV by in vivo methods and determine subtypes of TBEV. Blood samples were collected from 750 domestic animals in Khuvsgul, Selenge, Bulgan and Tuv aimags in 2012. After sample collection, a total of 184 sera were (horse 43, cattle 41, sheep 44, goat 56respectivel) randomly chosen and tested for antibodies against TBEV by c-ELISA and virus neutralization (VN) test. The c-ELISA results showed that 17 serum samples were positive and 25 -suspicious. In order to confirm c-ELISA result all these 42 serum samples were checked with VN test. The result of VN test showed 19/42 positive serum samples. In order to detect of TBEV in Mongolia, Ixodes persulcatus ticks were collected from Eruu sum, Selenge aimag and categorized into pools. Each pool was mixed with sterile PBS and homogenized with asterile mortar and pestle. The homogenate was centrifuged and the collected supernatant was inoculated into baby hamster kidney (BHK-21) cell line. Cytopathic effects (CPE) in the cell line was observed by light microscopy daily. RNA was extracted from supernatant of cells with CPE and confirmed by RT-PCR using specific primer for the Siberian subtype. The present results were indicated that TBEV in Mongolia was belonged to the Siberian subtype. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 19-26